TANTANGAN SANTRI BARU DALAM MENYIKAPI PERBEDAAN JADWAL SEKOLAH DAN PONDOK PESANTREN DI PAMEKASAN - Hariri, Moh; Listiana, Heny; Zuhud, Mohammad; Ihsan, Muhammad (Fakultas Agama Islam Universitas Islam Madura, 2024)
This article explores the adjustments new students must make at the Islamic boarding school due to a 53-day study delay. This delay is caused by the need to wait for their final exams at previous schools, stemming from a mismatch between the boarding school's and the government's academic calendars. Consequently, these students must catch up on the lessons they missed from the beginning of their textbooks. The study adopts a qualitative method and utilizes descriptive analysis at Miftahul Ulum Bettet Islamic Boarding School in Pamekasan. To resolve this issue, the school administration proposes various strategies.: (1) Conducting special tests to gauge new students' basic knowledge in religious studies. (2) Setting up special classes for new students to start from the beginning of the books. (3) Merging new students with existing classes while providing extra support to help them catch up. Effective supervision, direction, and coordination among boarding school administrators, formal school managers, and the students' guardians are vital to support the education who come from various different backgrounds.